Band alignment and charge transfer pathway in three phase anatase-rutile-brookite TiO2 nanotubes: an efficient photocatalyst for water splitting - Preethi, L. K.; Mathews, Tom; Nand, Mangla; Jha, S. N.; Chinnakonda, Gopinath S.; Dash, Sitaram (Applied Catalysis B-Environmental, 2017)
The study reports electrochemical synthesis, phase evolution and hydrogen generation efficiency of anatase, anatase-rutile and anatase-rutile-brookite (ARB) TiO2 nanotubes for the first time. The SEM and TEM micrographs confirm the tubular morphology of the samples. The presence of anatase, rutile and brookite phases in a single nanotube is confirmed from high resolution TEM analysis. The water splitting efficiency of the three systems are studied under one sun illumination. It is observed that the anatase-rutile-brookite TiO2 nanotubes are highly efficient compared to anatase-rutile or anatase TiO2 nanotubes. The hydrogen generated by ARB composites, after four hours of one sun illumination, is found to be nearly twice that of anatase TiO2 nanotubes and 1.6 times that of anatase-rutile TiO2 nanotubes. The results suggest that the ARB in single nanotube having two junction interfaces, highly facilitate interparticle charge transfer compared to single junction anatase-rutile or bare anatase TiO2 nanotubes. From the deconvolution of PL spectra and the synchrotron radiation assisted valence band edge analysis, the band diagram for the anatase-rutile-brookite phase is constructed. The charge separation and its transfer pathway for efficient photo-assisted water splitting are delineated. This opens a new route for the simple synthesis and study of tri-phase TiO2 for efficient photocatalytic water splitting compared to the widely studied two phase TiO2. (C) 2017 Published by Elsevier B.V.
Keywords: Anatase-Rutile-Brookite; Hydrogen generation; nanotubes; Photocatalysis; photoluminescence; Valence band edge

Operando X-ray absorption spectroscopy study of the Fischer-Tropsch reaction with a Co catalyst - Nayak, Chandrani; Jain, Preeti; Vinod, C. P.; Jha, S. N.; Bhattacharyya, D. (Journal of Synchrotron Radiation, 2019)
This article describes the setting up of a facility on the energy-scanning EXAFS beamline (BL-09) at RRCAT, Indore, India, for operando studies of structure-activity correlation during a catalytic reaction. The setup was tested by operando X-ray absorption spectroscopy (XAS) studies performed on a Co-based catalyst during the Fischer-Tropsch reaction to obtain information regarding structural changes in the catalyst during the reaction. Simultaneous gas chromatography (GC) measurements during the reaction facilitate monitoring of the product gases, which in turn gives information regarding the activity of the catalyst. The combination of XAS and GC techniques was used to correlate the structural changes with the activity of the catalyst at different reaction temperatures. The oxide catalyst was reduced to the metallic phase by heating at 400 degrees C for 5h under H-2 at ambient pressure and subsequently the catalytic reaction was studied at four different temperatures of 240, 260, 280 and 320 degrees C. The catalyst was studied for 10h at 320 degrees C and an attempt has been made to understand the process of its deactivation from the XANES and EXAFS results.
Keywords: catalysis; EXAFS; Fischer-Tropsch reaction; in situ studies; structure-activity correlation; XANES

Spectroscopic evidences for the size dependent generation of pd species responsible for the low temperature CO oxidation activity on Pd-SBA-15 nanocatalyst - Soni, Yogita; Pradhan, Sumanta; Bamnia, Mahesh K.; Yadav, A. K.; Jha, S. N.; Bhattacharyya, D.; Khan, Tuhin Suvra; Haider, M. A.; Vinod, C. P. (Applied Catalysis B-Environmental, 2020)
A comprehensive size dependent CO oxidation activity has been demonstrated for Pd-SBA-15 catalysts with Pd NPs of varying sizes such as 1-2, 4-6 and 7-10 nm. Pd-SBA-15 catalyst with smallest sized NPs (Pd-S-N) has been synthesized by modified deposition precipitation method recently developed in our lab. Pd-S-N catalyst (reduced at 400 degrees C) demonstrated CO oxidation activity with lower light off temperature (50 degrees C), clearly one of the best reported for a Pd-silica system. A detailed XPS and in-situ DRIFTS analyses further supported by XAS and DFT calculations reveal the presence of easily decomposable highvalent Pd-oxide on co-ordinatively unsaturated Pd sites (Pdcus). Weak binding of CO on Pdcus sites in small Pd NPs leaving sites for oxygen activation is attributed to the low temperature activity of Pd-S-N for CO oxidation.
Keywords: CO oxidation; high-valent Pd species; Pd nanoparticles; SBA-15; under coordinated Pd atoms

MnXWO4 nanostructure-based catalysts for single-step oxidation of cyclohexane and methane to oxygenates - Prabu, Marimuthu; Manikandan, Marimuthu; Samal, Pragnya Paramita; Gurrala, Lakshmi Prasad; Mekala, Siva Prasad; Archana, Ramakrishnan; Nayak, Chandrani; Bhattacharyya, D.; Jha, S. N.; Krishnamurty, Sailaja; Raja, Thirumalaiswamy (ACS Applied Nano Materials, 2023)
Activation of the C-H bond in cyclohexane (CYH) and methane is a crucial step to obtain desirable oxygenated products using nanostructured catalyst and is a great challenge and an efficient route to mitigate the inauspicious effects of climate change. The active sites were identified using XRD, HR-TEM, SEM, N2 sorption analysis, TPR, Raman, XPS, TGA, in situ DRIFT, XAS, etc. In optimal reaction conditions, 46% of CYH was converted into adipic acid (AA) on MnxWO4 nanostructures within 6 h. The recyclability test confirmed the catalyst heterogeneity, which revealed no appreciable loss of catalytic activity even after three consecutive reactions. In situ DRIFT study reveals that CYH is oxidized to cyclohexanone and cyclohexanol (KA oil) and is further oxidized to AA via carboxylate intermediates. DFT studies disclosed that MnOx species are responsible for the C-H activation of CYH, and the Mn2+/Mn3+ redox centers play a vital role in the absorption of KA oil to form AA. Herein, we demonstrated the significant role of the ``MnOx'' species and that adequate Lewis and Bronsted acidic sites, redox centers of (Mn2+/Mn3+), and lattice oxygen are accountable for the CYH conversion toward the AA. Additionally, we have reported the oxidation of methane to methanol (146 mu mole per gram of catalyst) in the presence of water at 75 degrees C without over-oxidation products.
Keywords: Adipic Acid; C-H bond activation; Cyclohexane oxidation; methane activation; MnOx chain; Redox center